(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Nursing care of newborns is a critical component of neonatal healthcare that focuses on promoting physiological stability, preventing complications, and supporting healthy growth and development during the first 28 days of life. The neonatal period is marked by rapid adaptation to extrauterine life, requiring continuous professional observation and evidence-based interventions. This abstract highlights the essential roles of nurses in maintaining thermoregulation, monitoring vital signs, ensuring adequate nutrition, and preventing infection in newborns. Effective thermoregulation is necessary because newborns are vulnerable to hypothermia due to immature temperature control mechanisms. Regular assessment of respiratory and cardiovascular parameters enables early detection of neonatal disorders. Nutritional support, particularly exclusive breastfeeding, provides optimal nutrients and immunological protection, while nursing guidance ensures proper feeding techniques and tolerance. Infection control remains a cornerstone of neonatal nursing practice through strict hygiene, umbilical cord care, and environmental safety. In addition, nurses play a key role in parent education, empowering families to recognize danger signs and provide appropriate care at home. High-quality nursing care contributes significantly to reducing neonatal morbidity and mortality and improving overall neonatal outcomes.